(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2024)
The article reveals the essence of human capital using various socio-economic, industrial, property, personal, distributive, institutional, social, reproductive approaches to its content and the place of education in it. The category of human capital is a complex structural object of socio-economic research. Human capital brings income to the employee in the form of salary, to the employer in the form of profit and to the state in the form of taxes. Therefore, human capital as an economic category represents the economic relations between the employee, the employer and the state on the labor potential and the distribution of income between them.